Educational Services Marketing in Customer Enhancement - Harmonisa Putri; Suci Fitriani; Bawaihi Bawaihi (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2023)
This study deals with the marketing of educational offerings at Madrasah Tsanawiyah Darul Arifin Muaro Jambi. The purpose of this work is to study the marketing of educational services used by Madrasah Tsanawiyah Darul Arif, Muaro Jambi. The collection of research data is poured in the form of qualitative descriptive through observation, interviews and documentation. Based on the author's observations, Madrasah Tsanawiyah Darul Arifin Muaro Jambi uses a marketing mix strategy in its marketing. The marketing mix strategy includes 7P, namely products, Madrasah Tsanawiyah products, namely for the price of English and Arabic language skills, according to the price set by the Madrasah Tsanawiyah, it is still moderate, location, the location of the Madrasah Tsanawiyah is quite strategic and easy to access, people, they have human resources (teachers and employees) who are qualified in their fields, Promotion, carry out promotional activities using social media, brochures, calendars and the installation of banners, Physical Facilities, the facilities and infrastructure owned by this madrasa are good enough to support teaching and learning activities, and the next is Process, teaching and learning activities at this tsnawiyah madrasah are carried out starting at 06:00: 00 WIB to 21:00. Supporting factors in conducting marketing are in the form of teachers who teach according to their areas of expertise, have students who have morals. While the inhibiting factors are the image of the madrasah, competitors and community interest.